Simulation - Fariba Haghani; Maryam Ehsani; Soheila Jafari Mianaei (Kerman University of Medical Sciences, 2014)
Background & Objective: Simulation is an educational technique which through providing whole or part of a clinical experience helps students to learn without being afraid of either their personal weaknesses or hurting the patient during interaction Manipulation of medical education is widely being spread all over the world and this can be due to various factors such as technological improvements ethical issues relating to practicing clinical skills crowdedness of clinical environments for educational purposes illness severity in most patients drop in the length of patients stay in the hospitals shortage of specialized staff in hospitals to facilitate educational process and so on   Methods: The current study has reviewed existing books library references papers and essays available in different scientific databases using keywords of "simulation" "medical education" and "clinical skills"   Results: Simulation offers several advantages including increase in patients safety reinforcement of interactive learning and studentcentered improvement in problemsolving abilities and critical thinking skills and selfpaced learning Despite all the abovementioned benefits the point is that due to the high costs of simulation equipment as well as improper cost management policies particularly in educational centers several studies should be run to analyze outcomes of manipulation of different simulators on students learning and then based on the efficiency of the simulators the proper ones be used for educational purposes in clinical environments